1976
DOI: 10.1083/jcb.68.1.159
|View full text |Cite
|
Sign up to set email alerts
|

Roles of creatine in the regulation of cardiac protein synthesis

Abstract: The observation that increased muscular activity leads to muscle hypertrophy is well known, but identification of the biochemical and physiological mechanisms by which this occurs remains an important problem. Experiments have been described (5, 6) which suggest that creatine, an end

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

1978
1978
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 13 publications
1
4
0
1
Order By: Relevance
“…In the Arg-adequate diet, however, the rate of muscle protein synthesis should be equivalent because all diets contained adequate and equal quantities of Arg, yet muscle concentrations of Cr-related metabolites continued to increase due to GAA supplementation. While this did not manifest as an improvement in BW gain in our study, this phenomenon has been previously reported to increase muscle growth (Ingwall, 1976; Ingwall and Wildenthal, 1976). Whereas 0.06 and 0.12% GAA supplementation elicited increases in the PCr:ATP and tCr:ATP ratios in both Arg-deficient and Arg-adequate diets, improvements in the Arg-deficient scenario were 2 to 3 times greater than when diets were Arg-adequate.…”
Section: Discussionsupporting
confidence: 46%
“…In the Arg-adequate diet, however, the rate of muscle protein synthesis should be equivalent because all diets contained adequate and equal quantities of Arg, yet muscle concentrations of Cr-related metabolites continued to increase due to GAA supplementation. While this did not manifest as an improvement in BW gain in our study, this phenomenon has been previously reported to increase muscle growth (Ingwall, 1976; Ingwall and Wildenthal, 1976). Whereas 0.06 and 0.12% GAA supplementation elicited increases in the PCr:ATP and tCr:ATP ratios in both Arg-deficient and Arg-adequate diets, improvements in the Arg-deficient scenario were 2 to 3 times greater than when diets were Arg-adequate.…”
Section: Discussionsupporting
confidence: 46%
“…When added to the bathing medium of differentiating skeletal and heart muscle cells in tissue culture, Cr increased rather specifically the rate of synthesis as well as the specific activity of myosin heavy chain (406,1153). In slices of the rat neostriatum, Cr inhibited the GABAsynthesizing enzyme glutamate decarboxylase as well as the veratridine-induced release of GABA, but significant effects were only observed at an unphysiologically high Cr concentration of 25 mM (864).…”
Section: Phosphocreatine and Creatine As Purported Allosteric Effmentioning
confidence: 99%
“…The underlying basis for this weight gain is still unclear. It may be due to stimulation of muscle protein synthesis (255,406,1153) or to increased water retention in the initial days of Cr supplementation (387,442). Because the proportion of fat tended to decrease and lean tissue weight increased with Cr supplementation (209,312,510,511,952,1040), the increase in body weight most likely reflects a corresponding increase in actual muscle mass and/or volume, a point that is particularly relevant for bodybuilders.…”
Section: Creatine Supplementation In Sports Physiologymentioning
confidence: 99%
“…However, several previous investigations have implicated a possible role for creatine in this process. Creatine has been reported to stimulate the incorporation of radioactive amino acids into myofibrillar proteins in both embryonic muscle-cell cultures and organ cultures (Ingwall et al, 1972;Ingwall & Wildenthal, 1976), although subsequent re-evaluation of these data was unable to demonstrate stimulation (Fry & Morales, 1980). The observations that electrical stimulation (Brevet et al, 1976) and Ca2+-ionophore treatment (Kameyama & Etlinger, 1979; stimulate myosin synthesis can also be rationalized as indirect actions of creatine.…”
mentioning
confidence: 97%